CHI '05 Extended Abstracts on Human Factors in Computing Systems 2005
DOI: 10.1145/1056808.1056894
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour, realism and immersion in games

Abstract: Immersion is recognised as an important element of good games. However, it is not always clear what is meant by immersion. Earlier work has identified possible barriers to immersion including a lack of coherence between different aspects of the game.Building on this work, we designed an experiment to examine people's expectations of how a game should behave and what would happen if that behaviour was deliberately made to be incoherent. The idea then is to understand immersion through seeing how immersion can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 5 publications
0
34
0
Order By: Relevance
“…Barriers to total immersion are a lack of empathy with game characters or a lack of feeling the atmosphere of the game. In a follow-up study [7], the stability of immersion is investigated. Here, the authors attempt to deliberately break the immersion of their test subjects and find that already low levels of immersion make subjects ignore drastic changes in the games behavior.…”
Section: Levels Of Immersionmentioning
confidence: 99%
“…Barriers to total immersion are a lack of empathy with game characters or a lack of feeling the atmosphere of the game. In a follow-up study [7], the stability of immersion is investigated. Here, the authors attempt to deliberately break the immersion of their test subjects and find that already low levels of immersion make subjects ignore drastic changes in the games behavior.…”
Section: Levels Of Immersionmentioning
confidence: 99%
“…These factors are also discussed in work on cognitive absorption [6]. There are examples of measuring immersion, the feeling of being pulled into and becoming lost in the interaction with a piece of technology [7,8], and qualitative work in examining the engagement of visitors with interactive exhibits [9]. Finally, there is flow [10], the concept of optimal experience where a user experiences feelings of satisfaction and achievement when the experience is complete.…”
Section: Introductionmentioning
confidence: 99%
“…But as research in the world of videogames has demonstrated, a certain degree of incoherence in the behavior of objects and things is admissible if immersion has previously been achieved (Cheng and Cairns, 2005). Or, put differently, if there is already a certain degree of immersion (for example, immersion in the story), this contributes to making up for other less successfully achieved aspects of perceptual realism.…”
Section: The Challenge Of Interactive Agencymentioning
confidence: 99%